(8)(16)=(6)(2x+6)

Simple and best practice solution for (8)(16)=(6)(2x+6) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (8)(16)=(6)(2x+6) equation:


Simplifying
(8)(16) = (6)(2x + 6)

Multiply 8 * 16
128 = (6)(2x + 6)

Reorder the terms:
128 = 6(6 + 2x)
128 = (6 * 6 + 2x * 6)
128 = (36 + 12x)

Solving
128 = 36 + 12x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-12x' to each side of the equation.
128 + -12x = 36 + 12x + -12x

Combine like terms: 12x + -12x = 0
128 + -12x = 36 + 0
128 + -12x = 36

Add '-128' to each side of the equation.
128 + -128 + -12x = 36 + -128

Combine like terms: 128 + -128 = 0
0 + -12x = 36 + -128
-12x = 36 + -128

Combine like terms: 36 + -128 = -92
-12x = -92

Divide each side by '-12'.
x = 7.666666667

Simplifying
x = 7.666666667

See similar equations:

| 4=3p+6-2p | | -9x=-10x | | -3=-5p+9+6p | | 1-0.7k=1 | | -9=7p-15-6p | | 12xy^2+1=0 | | 24=5X-7 | | 3=3p-4-2p | | 17+9s=2(8s-3) | | 30-5(p-10)=11 | | 16x^2+3=-16x | | -14=4p+7-3p | | 6x+10=2y+10 | | -14=-8p+5+9p | | (x+1)/(2-x)*(2-x)^2/(x-2)*2/x+1 | | -11w+6=-38 | | .24.14= | | 10=-2p-2+3p | | -4=-4p-11+5p | | M/-16=-9 | | y-9=15(x-5) | | 13=3p-15-2p | | x^2+24x-23=0 | | 8x^2-28x+98=0 | | 8x^2-28+98=0 | | 38x-14=20 | | 2(x-2)=-3x+21 | | 2+3.8= | | 3(2a-4)= | | 2(x-2)=-3+21 | | 3a+50=140 | | -9-6=8+x |

Equations solver categories